Reduction of Mutual Coupling for Broadband Vivaldi Antennas Using Characteristic Modes Analysis and Lumped Loads - Zhenpeng Ma; Qi Wu, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
A method to reduce mutual coupling for broadband Vivaldi antennas is presented in this paper. Theory of characteristic modes is used to analyze the surface currents on the Vivaldi antennas which may contribute to mutual coupling, and inductive loads are used to suppress these modes. Mutual coupling between adjacent Vivaldi antennas is reduced by 10~20 dB on average in a wide bandwidth. Three configurations, including the classical design, design with slot, and design with inductive loads are studied. Numerical and experimental results are presented to verify the effectiveness of this method, which ensures that the method has very little influence to normal operation of Vivaldi antennas.